Quantifying and characterizing degradation of dissolved organic carbon from aquaculture wastewater: a case study of Litopenaeus vannamei - Li, Yang; Huang, Hong; Zhu, Zhuo-Yi; Cheng, Peng-Fei; Zhao, Xu; Dang, Sheng-Nan (Frontiers in Marine Science, 2025)
As integral components of global ecosystems, aquaculture ponds have received limited research attention regarding the fate and transformation of dissolved organic matter (DOM) in their wastewater. In this study, an incubation experiment was conducted to simulate the degradation of dissolved organic carbon (DOC) in Litopenaeus vannamei aquaculture wastewater under three conditions: photodegradation, biodegradation, and a combination of both photodegradation and biodegradation. We measured the concentration of DOC, the ultraviolet-visible absorbance, and the excitation-emission matrix (EEM) of aquaculture wastewater during the incubation. Based on the changes in DOC, we further estimated the upper limit of CO2 emissions from the aquaculture wastewater. The source of organic matter in the samples was identified by Parallel Factor Analysis (PARAFAC). Subsequently, Principal Component Analysis (PCA) was employed to reveal the differential effects of various degradation conditions on the composition of organic matter. The results demonstrated that under combined photodegradation and biodegradation, DOC in aquaculture wastewater exhibited a degradation rate of approximately 19% over 29 days. Based on this degradation efficiency, we estimated that the upper limit of CO2 emissions from the system amount to 0.7 kg CO2-eq per kg DOC, suggesting that aquaculture wastewater may act as a potential carbon source. Analysis of optical parameters revealed distinct roles of degradation mechanisms: light primarily altered the structural complexity of organic matter, whereas microorganisms directly reduced DOC concentrations and generated new metabolites. Fluorescence characterization via EEM combined with PARAFAC identified four components in the wastewater: C1 (microbial humic-like), C2 (terrestrial humic-like), C3 (autochthonous tyrosine-like) and C4 (terrestrial humic-like, distinct from C2 in spectral properties). PCA of 11 parameters in the incubation experiment showed that photodegradation weakened the stability and humification degree of organic matter, and produced products with simpler structures. Biodegradation has little effect on the stability and humification of organic matter, and is mainly characterized by the production of fresh low molecular weight (LMW) metabolites. The results of this study contribute to understanding the stability of DOC from aquaculture wastewater and reveal the differential effects of different degradation processes on organic matter composition, providing a basis for understanding the transformation pathways of organic matter in the environment.